Implementation of Contextual Teaching and Learning in MA Muhammadiyah Paciran Lamongan - Hudzaifa Ahmad; Zainuddin Maliki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The quality of life of a nation is largely determined by the factor of education. The role of education is very important to create an intelligent, peaceful, open and democratic life. Religious education must be used as a benchmark in shaping the character and personality of students, as well as building national morale. So that in its implementation, Islamic religious education must be carried out as well as possible with mature management and directed to the continuity of human relations with his creator, humans with humans (society) and humans with their natural surroundings. This study aims to discuss how the implementation of Contextual Teaching and Learning in MA Muhammadiyah Paciran Lamongan. This research uses a qualitative approach. Data collection using interview, observation and documentation techniques. The collected data is checked for validity with source and method triangulation techniques, data checking and peer discussion. Data were analyzed by taking steps; (1) data reduction (2) data presentation and (3) conclusion drawing. From the results of data analysis research the following findings can be obtained: First, the planning of CTL-based Islamic Religious Education learning strategies at MA Muhammadiyah Paciran Lamongan has been carried out with proper and correct planning. This is evidenced by the creation of an annual program (prota), semester program (promissory) and a learning plan program (RPP). Second, the implementation of CTL-based Islamic Religious Education learning strategies in MA Muhammadiyah Paciran Lamongan has been carried out optimally. This is based on the application of the seven main components of CTL learning strategy implementation, among others; constructivism, questioning, inquiry, learning community, modeling, reflection and authentic assessment. Keywords: Islamic education, Contextual Teaching and Learning, MAM Paciran